Desain Sistem Informasi Akuntansi Berbasis Komputer untuk Penyusunan Laporan Keuangan Menggunakan Microsoft Access 2010 - Surya Sukmawan Sinatriyo; A. Andriana; K. Kartika (UPT Penerbitan Universitas Jember, 2019)
This study aims to design a computer-based accounting information system for the preparation of financial statements using Microsoft Access 2010 on the small medium companythat provide network, cctv installation services and also trading computer components namely CV. Satria Computindo. This research used descriptive qualtitative. Methods of data collection is done by interview and documentation, and testing the validity of data used in the form of source triangulation, time triangulation, and membercheck. Accounting system used were selling, cash receiveing and cash disburshment and sallary and payroll accounting system. Design of computer-based accounting information systems to support the preparation of financial statements using Rapid Application Development (RAD) techniques that develop the system in a short period of time using prototyping. Applications used for system development is using Microsoft Access which includes table design, creation of relations between tables, query design, form design, and report design. This study is expected to reduce the occurrence of recording errors caused by human factors, accelerate the acquisition of financial information for the leadership and accelerate the real time acquisition of stock information. Keywords: Accounting Information System, Financial Statements, Microsoft Access 2010, Prototyping, Rapid Application Development – RAD.